2022
DOI: 10.3390/plants11141837
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effect of the compactum Gene and Its Combined Effects with Other Loci for Spike and Grain-Related Traits in Wheat

Abstract: Club wheat (Triticum aestivum ssp. compactum) with a distinctly compact spike morphology was conditioned by the dominant compactum (C) locus on chromosome 2D and resulted in a redistribution of spike yield components. The disclosure of the genetic basis of club wheat was a prerequisite for the development of widely adapted, agronomically competitive club wheat cultivars. In this study, we used a recombinant inbred line population derived from a cross between club wheat Hiller and modern cultivar Yangmai 158 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Besides using static and dynamic phenotypes to study N responsiveness and N-response phenotypes, we further explored the use of dynamic phenotyping to associate genetics underlying N responsiveness. GWAS was performed using the Wheat55K SNP Array [ 57 , 70 ]. After removing low-quality markers, 44,215 SNP markers were obtained, covering 13,531.8 Mb (Table S12 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides using static and dynamic phenotypes to study N responsiveness and N-response phenotypes, we further explored the use of dynamic phenotyping to associate genetics underlying N responsiveness. GWAS was performed using the Wheat55K SNP Array [ 57 , 70 ]. After removing low-quality markers, 44,215 SNP markers were obtained, covering 13,531.8 Mb (Table S12 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To date, the putative location of the C-locus was identi ed as C-2DS or C-2DL (Johnson et al 2008;Yu et al 2022;Wen et al 2022). Some recent studies have also used different approaches to localize the Clocus without any consensus on a single arm of the chromosome 2D.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of mapping studies were conducted on this trait and there is no consensus about the placement of the C-locus (Johnson et al 2008;Yu et al 2022;Wen et al 2022). Johnson et al 2008, used two genetic mapping populations and placed the C-locus close to the centromeric region of chromosome 2D.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vrn-3 produces a mobile protein that functions as a flowering activator [26] and, as homologous to FLOWERING LOCUS T (FT) of Arabidopsis [26,41], is induced by long days, further accelerating reproductive apex development [26,38,42]. In hexaploid wheat, the three copies of Vrn-3 (Vrn-A3, Vrn-B3, and Vrn-D3) were mapped on chromosomes 7A, 7B, and 7D, respectively [26,[43][44][45][46]. Yan et al [26] first suggested that Vrn-3 was linked to a gene similar to Arabidopsis FT; the latter was then proposed by Tamaki et al [47] as the candidate for Florigen, a locus encoding the mobile signal that induces floral initiation at the shoot apex [47].…”
Section: Characteristics and Functions Of Vrn Genesmentioning
confidence: 99%